PENGARUH SERTIFIKASI TANAH UKM TERHADAP PENDAPATAN RUMAH TANGGA PETERNAK PENGGEMUKAN SAPI DI DESA RAJABASA LAMA 1 KECAMATAN LABUHAN RATU KABUPATEN LAMPUNG TIMUR - Siswandari, Gama Ayu; Ismono, Hanung; Santoso, Hurip (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
Land certification of SME’s (small and micro enterprises) contributes to household income of feed lot farmers in Rajabasa Lama 1 Village Labuhan Ratu District of East Lampung Regency. The purposes of this study were to determinethe utilization of SME’s land certification in the sustainability of feedlot farming, and incomes of feedlot farmerland certification users and nonusers. Data used are primary and secondary data. This study uses analysis of household income and independent sample t test for different test of household income. The results showed that the use of land certification in sustainability of SME’s in the cattle is as capital to buy seeds. The phases of feedlot farming performance includes seed selection,manufacture of barn, feeding, disease and health care, crop and cattle manure from cow dung. The average income of farmers whohave certified land of SME’s with average of 7 cows and income of farmers whohave certified land of SME’s with average of 7 cows are Rp15,732,847.00 and Rp 21,249,680.00. These results indicates a significant difference in cost(P <0.05). It can be concluded that there is a difference in income generated in the average number of cows between farmers using certified land and those who don’t. Key words: beef cattle, cattle, household income, land certification SME’s, rancher